Kuya Ngagandong Imahna: Analisis Keterampilan Membaca Dongeng Bahasa Sunda pada Siswa Sekolah Dasar - Siti Rizki Nuranissa; Astri Sutisnawati; Luthfi Hamdani Maula (STKIP Andi Matappa Pangkep, 2023)
The research aimed at knowing, analyzing, and explicitly describing the reading skills of elementary school students, especially in reading Sundanese text entitled Kuya Ngagandong Imahna. Data collection through oral reading test and observation. Referring to the acquisition of oral reading test scores, the reading skills of the students can be said to be quite fluent in reading Sundanese fairy tales entitled Kuya Ngagandong Imahna. The end result is that students are able to identify letters correctly, pronounce words fairly accurately, read fluently and answer questions about the content of the reading correctly.